2022
DOI: 10.1007/s11119-022-09930-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of precision and conventional irrigation in corn production in Southeast Alabama

Abstract: Adoption of water-conservation irrigation practices could potentially reduce water and energy use and increase profitability, as well as protect the environment. Precision irrigation consisting of soil sensors (SS) for irrigation scheduling and variable rate irrigation (VRI) was compared with conventional uniform irrigation (URI). The study was conducted in South Alabama during the 2018 and 2019 corn growing seasons. The SS-VRI and URI treatments spanned the length of the field and were compared across five di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In France, this number is likely even lower because forage maize acres are managed by smaller farms with less access to the training and materials needed to monitor soil water tension. In trials comparing conventional and precision irrigation, full yield recovery was possible while water use for grain was reduced by 25% ( Bondesan et al., 2023 ). Clearly, even a relatively small reduction in stress can easily contribute to recovery of productivity.…”
Section: Discussionmentioning
confidence: 99%
“…In France, this number is likely even lower because forage maize acres are managed by smaller farms with less access to the training and materials needed to monitor soil water tension. In trials comparing conventional and precision irrigation, full yield recovery was possible while water use for grain was reduced by 25% ( Bondesan et al., 2023 ). Clearly, even a relatively small reduction in stress can easily contribute to recovery of productivity.…”
Section: Discussionmentioning
confidence: 99%
“…From visual comparisons, Figures 8 and 9 could not reveal insight about the reasons for varying irrigation MZs within the field since there was no sign of correlation between the variations in MZs and NDVI or soil texture. Previous research has also concluded that NDVI data alone are not sufficient to make decisions in irrigation management [44]. More data, such as spatial emergence rate, plant density, leaf area index, and pest (weed and disease) pressure on plant growth, may reveal the necessary information to explain the cause of varying irrigation management zones.…”
Section: Vri Maps For Hose Reel Irrigation Machinementioning
confidence: 99%
“…However, the vast majority of drip irrigation systems remain to a certain extent “rudimentary”, due to the low adoption of technology and tools by farmers ( Bondesan et al., 2023 ). Smart systems still need to become more accessible and user-friendly for farmers to boost their adoption ( Li and Wang, 2021 ).…”
Section: Introductionmentioning
confidence: 99%